PELATIHAN PENGOLAHAN IKAN SEBAGAI UPAYA EKONOMI KREATIF DI MASA PANDEMI COVID-19 KEPADA IBU-IBU MAJELIS TA’LIM SULTRA - Cornelia Pary; Nana Ronawan Rambe; Heni Mutmainnah; Laila sahubawa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2021)
The objectives of this community service are 1) To increas the Knowledge of the Sultra Ta'lim council women about Nutrition and processing of fish into shredded fish, chili Rowa, fish balls and fish nuggets, 2) To train the Sultra Ta'lim Council women to process fish becomes healthy and nutritious ready to eat food at home that can be commercialized as a source of income to increase income during the Covid-19 pandemic. This service activity is carried out in the form of systematically structured training to improve the abilities of Sultra Ta'lim assemblies. in processing fish with various kinds of processed materials and practices presented and guided by lecturers as facilitators / presenters and students as executors. The results obtained were 1. The knowledge of the Sultra Ta'lim council members increased about nutrition and processing of fish into shredded fish, chili Rowa, fish balls and fish nuggets, 2. The Sultra Ta'lim council women could process fish into ready to eat food healthy and nutritious at home that can be commercialized as a source of income to increase income during the Covid-19 pandemic